(untitled) (Research, Society and Development, 2022)
The objective of this work was to evaluate the efficiency of green pruning in different cultures and cultivars of cucurbits, aiming at an increase in the production of flowers and fruits. watermelon ´´Citrullus lanatus`` and melon ``Cucumis melo`` were used. the experiment was implemented in the region of telemaco borba (pr) in a randomized block design with 5 reptiles, 3 watermelon cultivars (flairflex, crinson sweet and congo) and 1 melon cultivar (caipira), for evaluation criteria the fruits were harvested and in the laboratory the values of soluble solids, brix, ph and ratio were determined. and for production criteria, values of weight, height and diameter were determined.